Desenvolvimento de uma ferramenta móvel para auxílio na gestão de resíduos de construção civil em canteiros de obra - Cordeiro, Ana Regina Jafra (2022)
A recurring problem in the construction market is the impact caused by civil construction waste (RCC) since they present themselves in different ways, which can be environmental, social, sanitary, visual, and economic. Among many factors that corroborate this situation, the most critical is the need for planning and more efficient management, with correct and more accessible information. In this way, this work proposes to develop a new tool that helps the management of civil construction waste, through the development of a new technology that promotes the proper and more efficient destination of these materials. Therefore, the Management Plans required by the National Solid Waste Policy (PNRS) and the definitions established in CONAMA Resolution n°307/2002 were used as a basis for instrumentation, proposing interventions that promote reduction, reuse and recycling of these solid wastes. These measures were defined from the literature review, document analysis and quantitative and qualitative research of current projects. With this, the main deficiencies in construction waste management projects were identified, which showed the need to have greater access and greater control of management information, as well as the possibilities of using this waste that avoiding its disposal. Therefore, the objective of this work was to develop an application that works as a mobile tool capable of diagnosing the generation of civil construction waste at construction sites and analyzing the recycling potential, in addition to the adequate destination of this material, promoting the instruction of the professional responsible for the disposal of RCC for the most correct way to dispose of them. Thus, the Application ReciclaObra proved to be efficient for its purpose of assisting in the management of construction waste in construction sites. Moreover, the tool showed to be able to expand the accessibility of professionals to the inserted content, being this information about civil construction waste, how to perform proper segregation, the best form of storage and sorting, the possible disposals, how to perform the disposal correctly, in addition to following and elaborating the Waste Management Plan, all of this in an easy and practical way.